Separation of foot and mouth disease virus neutralizing antibodies by ion exchanger - ΔΗΜΗΤΡΙΑΔΗΣ Ι. Α. (Journal of the Hellenic Veterinary Medical Society, 2019)
Using chromatography with ion exchanger DEAE-50, Foot and Mouth Disease types, Ο,Α and C neutralizing antibodies were separated from hyperimmune cattle serum. The first fraction (Fraction No 0) behaves in electrophoresis and immune electrophoresis (slow movement to the anod) like Ig G2 and its neutralizing antibodies titre is higher than in the other ftactions (Fraction No 1-4) corresponding to Ig G,. From the fractions of the hyperimmune serum, which were tested, Foot and Mouth Disease types A and Ο neutralizing antibodies were isolated with relatively low titres. The same serum tested as whole serum had Food and Mouth Diesease neutralinzing anutibodies of types A, Ο and C 1:216, 1:512 and 1:32 respectively. The fraction No 1-4 of the serum behaving in electrophoresis like Ig G. unlike Ig G, of the colostrum, did not show the hemocytotropism phenomenon.